MUZAKI BEHAVIOR IN PAYING ZAKAT THROUGH THE APPLICATION OF THE UNIFIED THEORY MODEL ACCEPTANCE AND USE OF TECHNOLOGY IN JAKARTA PROVINCE - Tukhas Shilul Imaroh; Lasmi Indaryani; I Putu Doddy; Anita Setyastuti (TEKNOKOM, 2022)
This paper investigated the intents and behavior of muzakki who pay zakat through e-zakat using the Unified Theory of Acceptance and Use of Technology (UTAUT). In DKI Jakarta, the study was done. This article utilizes sampling convenience. The research data were collected using a questionnaire-based survey. Using SmartPLS 3.0, route analysis serves as a statistical instrument for evaluating hypotheses. . The findings indicated that neither the performance expectation variable nor the social influence variable substantially affected the desire to use e-zakat. The variable business expectation had a substantial beneficial impact on both the willingness to use e-zakat and the conditions that allow for a substantial beneficial impact on e-zakat use behavior.